Hybrid palm-oil/styrene-maleimide nanoparticles synthesized in aqueous dispersion under different conditions. (June 2015) - Samyn, Pieter; Van Nieuwkerke, Dieter; Schoukens, Gustaaf; Stanssens, Dirk; Vonck, Leo; Van den Abbeele, Henk
Abstract Poly(styrene-co-maleic anhydride) was imidized with ammonium hydroxide and palm oil, resulting in an aqueous dispersion of hybrid nanoparticles with diameters 85–180 nm (dispersed) or 20–50 nm (dried). The reaction conditions were optimized for different precursors by evaluating the relative amount ammonium hydroxide and maximizing the incorporated palm oil up to 70 wt.%. The interactions between palm oil and polymer phase have been studied by TEM, IR, Raman spectroscopy and thermal analysis (TGA, [TM] DSC). From Raman spectra, the amount of imide and reacted oil were quantified. Through concurring effects of imidization and coupling of fatty acids, the imidization needs a slight excess of NH3 relatively to maleic anhydride. The oxidative stability highly depends on oxidative crosslinking of free or non-reacted oil. Comparing the imide content from spectroscopic and thermal analysis suggests that a complex rigid imide phase without strong relaxation behavior has formed in combination with oil.